A method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate

The method controls calcium carbonate crystal size through primary and secondary form control steps, enhancing hiding power and whiteness, allowing calcium carbonate to replace titanium dioxide as a pigment effectively.

CN118771434BActive Publication Date: 2025-01-03GUANGXI HAORUI NANO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411001984.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-01-03
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

Existing methods for preparing calcium carbonate crystals fail to accurately control the particle size range, leading to unstable performance and inability to replace titanium dioxide as a pigment due to insufficient control of crystal form and hiding power.

Method used

A method involving primary and secondary crystal form control steps using specific agents like xylitol and sorbitol, combined with precise control of reaction conditions, to produce large cubic ultrafine precipitated calcium carbonate with a controlled particle size range of 0.5-0.6 μm.

Benefits of technology

The method achieves improved hiding power and whiteness, enabling calcium carbonate to partially replace titanium dioxide as a pigment, with stable crystal performance and cost-effective production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771434B_ABST
    Figure CN118771434B_ABST
Patent Text Reader

Abstract

The present application provides a preparation method of pigment-grade large cubic ultrafine precipitated calcium carbonate, which mainly includes five steps of primary aging, primary crystal form control, secondary aging, secondary crystal form control, and homogenization and powder making. Different crystal form control agents are added in the primary crystal form control and secondary crystal form control steps. During the primary crystal nucleus control process, the primary crystal form control agent can be directionally adsorbed on the surface of calcium carbonate to induce the generation of cubic crystal nuclei. During the secondary crystal nucleus control process, the secondary crystal form control agent undergoes a grafting reaction on the surface of the cubic crystal nucleus to further generate cubic calcium carbonate crystals with larger particle sizes. The average particle size range of the calcium carbonate crystals is accurately controlled within 0.5-0.6 μm, thereby improving its hiding power and whiteness, so that it can partially replace titanium dioxide as a high-performance pigment. The method has the advantages of simple operation, high precision in controlling the crystal particle size range, stable crystal performance, and easy promotion and implementation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of precipitated calcium carbonate preparation, and specifically relates to a method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate. Background Art

[0002] In the prior art, titanium dioxide is an important white pigment, which is widely used in coatings, plastics, paper, rubber and other industries. In the coatings industry, titanium dioxide has become an indispensable key raw material due to its excellent hiding power, stability and weather resistance, but due to the complex production process and high cost, it will greatly increase the cost of industrial products such as coatings.

[0003] In the prior art, calcium carbonate is a new type of inorganic filler with the largest usage and the widest application. It has the advantages of wide raw material sources, low price and high whiteness. It is widely used in rubber, plastic, papermaking, sealing adhesives, coatings, wires, cables, inks, welding rods, organic synthesis, metallurgy, glass, asbestos industry, medicine, food, daily chemicals, feed and other industries.

[0004] In the prior art, calcium carbonate crystals can be divided into light activated calcium carbonate, fine activated carbonate tubes and nano calcium carbonate according to the distribution of crystal particle size range. When the calcium carbonate crystal particle size distribution is ≥2μm, the calcium carbonate crystal is almost a spindle, and the hiding power and whiteness are low. When the calcium carbonate crystal particle size distribution is ≤100nm, the transparency of the calcium carbonate crystal is significantly improved, and the hiding power and whiteness are significantly reduced.

[0005] In the prior art, a crystal form control agent is usually used to adjust the particle size range of calcium carbonate crystals. However, since the types of crystal form control agents added in the prior art and the crystal form control process steps are too single, it is impossible to accurately control the particle size range of calcium carbonate crystals, and thus it is impossible to significantly improve its whiteness and hiding power, and it is impossible to partially replace titanium dioxide as a pigment and reduce the production cost of other industrial products such as coatings. Therefore, improvements are urgently needed. Summary of the invention

[0006] In order to solve the problems in the prior art that titanium dioxide has a high cost, the hiding power and whiteness of calcium carbonate powder are affected by the range of its crystal particle size, and in the actual production process, a crystal form controller is needed to control its particle size range. However, in the prior art, the crystal form controller and the crystal form control process steps are too simple, and the particle size range of calcium carbonate crystals cannot be controlled within the range of 200-1000nm, which makes the performance of calcium carbonate powder unstable and cannot partially replace titanium dioxide as a pigment. A preparation method of pigment-grade large cubic ultrafine precipitated calcium carbonate is proposed.

[0007] In order to solve the technical problem raised by the present application, the present application adopts the following scheme, a method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate, comprising the following steps:

[0008] Step 101. Primary aging:

[0009] Quicklime with a whiteness of 93-95 degrees and water are sequentially added into a reactor in a mass ratio of 1:5-7 to obtain reaction slurry A after digestion, and the reaction slurry A is filtered through a 180-250 mesh vibrating screen and then transferred to a three-stage suspension separator for impurity removal, and after the impurity removal is completed, it is filtered through a 280-350 mesh vibrating screen to obtain high-whiteness calcium hydroxide refined slurry, and the high-whiteness calcium hydroxide refined slurry is aged;

[0010] Step 102. Primary crystal form control:

[0011] After diluting the high-whiteness calcium hydroxide refined slurry after aging in step 101 to a concentration of 1.0-1.2 mol / L, a primary crystal form control agent is added at 40-45° C., and a reaction slurry B is obtained after a pre-reaction of 10-25 minutes. The reaction slurry B is transferred to a high-shear carbonization kettle, and carbonized once at a stirring frequency of 40-100 Hz and under the condition of introducing lime kiln gas. During the primary carbonization process, the conductivity of the reaction slurry B is measured to determine the reaction endpoint of the primary carbonization. After the primary carbonization reaches the reaction endpoint, the reaction slurry C is obtained;

[0012] Step 103. Secondary aging:

[0013] Adding an aging dispersant to the reaction slurry C obtained in step 102, aging for 36-72 hours at 90-100° C. and a stirring frequency of 15-30 Hz to obtain a reaction slurry D;

[0014] Step 104. Secondary crystal form control:

[0015] After diluting the reaction slurry D obtained in step 103 to a concentration of 1.0-1.2 mol / L, a secondary crystal form control agent is added at 40-45° C., and a reaction slurry E is obtained after a pre-reaction of 10-25 minutes. The reaction slurry E is transferred to a high shear carbonization kettle, and secondary carbonization is performed under the condition of a conductivity of 1.5-2.5 and continuous introduction of lime kiln gas. During the secondary carbonization process, the pH value of the reaction slurry E is measured to determine the reaction endpoint of the secondary carbonization. After the secondary carbonization reaches the reaction endpoint, a calcium carbonate slurry is obtained;

[0016] Step 105. Homogenization and milling:

[0017] After adding a homogenizing dispersant to the calcium carbonate slurry prepared in step 104, stirring for 30-50 minutes at room temperature and a stirring frequency of 10-30 Hz, the slurry is transferred to a homogenizing tank for homogenization. The homogenized slurry is dehydrated, dried, crushed and classified in sequence to obtain pigment-grade large cubic ultrafine precipitated calcium carbonate.

[0018] Furthermore, in step 102, the primary crystal form controlling agent is xylitol; by selecting xylitol linear monosaccharide as the primary crystal form controlling agent, it can be directionally adsorbed on the crystal surface of calcium carbonate and induce the slurry to synthesize regular cubic calcium carbonate.

[0019] Furthermore, in step 102, the flow rate of lime kiln gas is 0.3-0.5m 3 / min, the volume fraction of carbon dioxide in the lime kiln gas is 35-38%. By controlling the flow rate of lime kiln gas and the amount of carbon dioxide entering the carbonization kettle, on the one hand, the resource rate can be improved, the lime kiln gas can be effectively utilized, and atmospheric pollution can be avoided. On the other hand, the contact area between carbon dioxide and slurry can be controlled through the lime kiln gas, and then the crystal form and particle size range of calcium carbonate can be accurately controlled in combination with the crystal form control agent, so as to further improve the efficiency and sustainability of calcium carbonate production.

[0020] Furthermore, in step 102, when the conductivity of the reaction slurry B is measured to be 1.5-2.5, the primary carbonization reaction is completed to the end point, and the introduction of lime kiln gas is stopped. By controlling the conductivity, the activity and concentration of the ions in the slurry can be controlled, thereby ensuring that after the crystal form control agent is added to the slurry, the rapid generation of crystal nuclei is accurately controlled, and the continuous growth of subsequent crystals is ensured to obtain calcium carbonate crystals with the expected morphology and size.

[0021] Furthermore, the aging dispersant in step 103 is ammonium bicarbonate, and the amount of the aging dispersant added is 3-5% of the dry weight of calcium carbonate. By using ammonium bicarbonate as the aging dispersant, during the aging and dispersing process, ammonium bicarbonate can be adsorbed in the irregular gaps on the surface of calcium carbonate in the weakly alkaline calcium carbonate suspension, and a grafting reaction occurs, and calcium carbonate is grafted on the surface of calcium carbonate again, thereby repairing the surface of calcium carbonate and enlarging the calcium carbonate particles to form large cubic calcium carbonate, thereby achieving the dual purpose of improving dispersion and further controlling the particle size range of crystalline carbonate crystals.

[0022] Furthermore, in step 104, the secondary crystal form controlling agent is sorbitol. By using sorbitol as the secondary crystal form controlling agent, it is directionally adsorbed on the crystal surface of calcium carbonate, and the particles are exchanged with the newly injected calcium hydroxide to generate small cubic crystal nuclei, which are grafted on the surface of the calcium carbonate crystal, thereby further generating cubic calcium carbonate particles with larger particle size, ensuring that the particle size range of the calcium carbonate crystal is 20-100nm.

[0023] Furthermore, in step 104, the reaction slurry E is divided into two parts, one of which is directly transferred to the carbonization kettle, and lime kiln gas is continuously introduced therein, and the lime kiln gas flow rate and the volume fraction of carbon dioxide in the lime kiln gas are the same as those in step 102, and the other part is sprayed into the carbonization kettle through a spiral nozzle.

[0024] Furthermore, in step 104, the output flow rate of the spiral nozzle is 0.5-1m 3 / min, by dividing the reaction slurry E into two parts and outputting one of them through the spiral nozzle, the contact area between the slurry and carbon dioxide can be increased, the grafting of the slurry with the surface of the crystal nucleus can be promoted, the crystal growth can be promoted, and the crystal shape and particle size range can be accurately controlled.

[0025] Furthermore, in step 104, when the pH value of the reaction slurry E is measured to be 6.5-7.0, the secondary carbonization reaction reaches the end point and the introduction of lime kiln gas is stopped.

[0026] Furthermore, in step 105, the homogenizing dispersant is a mixture of phosphate ester and HOMOGENOLL-18 polycarboxylic acid surfactant in a mass ratio of 3-5:1, and the amount of the homogenizing dispersant added is 3-4% of the dry weight of calcium carbonate.

[0027] Compared with the prior art, this application has the following beneficial effects:

[0028] The present application provides a method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate, which mainly includes five steps of primary aging, primary crystal form control, secondary aging, secondary crystal form control, and homogenization and powder making. Different crystal form control agents are added in the primary crystal form control and secondary crystal form control steps. During the primary crystal nucleus control process, the primary crystal form control agent can be directionally adsorbed on the surface of calcium carbonate to induce the generation of cubic crystal nuclei. During the secondary crystal nucleus control process, the secondary crystal form control agent undergoes a grafting reaction on the surface of the cubic crystal nucleus to further generate cubic calcium carbonate crystals with larger particle sizes. The average particle size range of the calcium carbonate crystals is accurately controlled within a range of 0.5-0.6 μm, thereby improving its hiding power and whiteness, so that it can partially replace titanium dioxide as a high-performance pigment. The method has the advantages of simple operation, high precision in controlling the crystal particle size range, stable crystal performance, and easy promotion and implementation. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for describing the embodiments.

[0030] Figure 1 is a SEM image of the calcium carbonate crystals prepared in Example 1 of the present application;

[0031] Figure 2is a SEM image of the calcium carbonate crystals prepared in Example 2 of the present application;

[0032] Figure 3 This is a SEM image of the calcium carbonate crystals prepared in Example 3 of the present application. DETAILED DESCRIPTION

[0033] Combined with Figure 1-3 As shown, the technical solution is further described;

[0034] Example 1

[0035] A method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate comprises the following steps:

[0036] Step 101. Primary aging:

[0037] Quicklime with a whiteness of 94 degrees and water are sequentially added into a reactor in a mass ratio of 1:5 to obtain reaction slurry A after digestion, and the reaction slurry A is filtered through a 195-mesh vibrating screen and transferred to a three-stage suspension separator for impurity removal, and after impurity removal, it is filtered through a 300-mesh vibrating screen to obtain high-whiteness calcium hydroxide refined slurry, and the high-whiteness calcium hydroxide refined slurry is aged;

[0038] Step 102. Primary crystal form control:

[0039] After the aged high-whiteness calcium hydroxide refined slurry in step 101 is diluted to a concentration of 1.0 mol / L, 1.5% xylitol based on the dry weight of calcium carbonate is added at 40° C., and a reaction slurry B is obtained after a pre-reaction of 11 minutes. The reaction slurry B is transferred to a high-shear carbonization kettle, and carbonized once under the condition of a stirring frequency of 45 Hz and the introduction of lime kiln gas. When the conductivity of the reaction slurry B is measured to be 1.9, the introduction of lime kiln gas is stopped to obtain a reaction slurry C, wherein the flow rate of the lime kiln gas is 0.3 m 3 / min, the volume fraction of carbon dioxide in lime kiln gas is 35.1%;

[0040] Step 103. Secondary aging:

[0041] Adding ammonium bicarbonate to the reaction slurry C obtained in step 102, aging at 92° C. and stirring at 18 Hz for 40 hours to obtain a reaction slurry D, wherein the amount of ammonium bicarbonate added is 3% of the dry weight of calcium carbonate;

[0042] Step 104. Secondary crystal form control:

[0043] After the reaction slurry D obtained in step 103 is diluted to a concentration of 1.0 mol / L, 1.5% sorbitol by dry weight of calcium carbonate is added at 40° C., and the reaction slurry E is obtained after pre-reaction for 12 minutes. The reaction slurry E is transferred to a high shear carbonization kettle, and secondary carbonization is carried out under the condition of a conductivity of 1.8 and continuous introduction of lime kiln gas. When the pH value of the reaction slurry E is measured to be 6.8, the introduction of lime kiln gas is stopped to obtain a calcium carbonate slurry, wherein the reaction slurry E is divided into two parts, one of which is directly transferred to the carbonization kettle, and lime kiln gas is continuously introduced therein, and the lime kiln gas flow rate is 0.3m 3 / min, the volume fraction of carbon dioxide in the lime kiln gas is 35.3%, and the other part is passed through the spiral nozzle at 0.7m 3 The output flow rate of / min is sprayed into the carbonization kettle;

[0044] Step 105. Homogenization and milling:

[0045] After adding a homogenizing dispersant to the calcium carbonate slurry prepared in step 104, stirring for 32 minutes at room temperature and a stirring frequency of 15 Hz, the mixture is transferred to a homogenizing tank for homogenization. The homogenized slurry is sequentially dehydrated, dried, crushed and classified to obtain pigment-grade large cubic ultrafine precipitated calcium carbonate, wherein the homogenizing dispersant is a mixture of a phosphate ester and a HOMOGENOLL-18 polycarboxylic acid surfactant in a mass ratio of 3:1, and the amount of the homogenizing dispersant added is 3% of the dry weight of the calcium carbonate.

[0046] Example 2

[0047] A method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate comprises the following steps:

[0048] Step 101. Primary aging:

[0049] Quicklime with a whiteness of 94 degrees and water are sequentially added into a reactor in a mass ratio of 1:6 to obtain reaction slurry A after digestion, and the reaction slurry A is filtered through a 200-mesh vibrating screen and transferred to a three-stage suspension separator for impurity removal, and after impurity removal, it is filtered through a 325-mesh vibrating screen to obtain high-whiteness calcium hydroxide refined slurry, and the high-whiteness calcium hydroxide refined slurry is aged;

[0050] Step 102. Primary crystal form control:

[0051] After the aged high-whiteness calcium hydroxide refined slurry in step 101 is diluted to a concentration of 1.05 mol / L, 1.5% xylitol based on the dry weight of calcium carbonate is added at 42° C., and a reaction slurry B is obtained after a pre-reaction for 18 minutes. The reaction slurry B is transferred to a high-shear carbonization kettle, and carbonized once under the condition of a stirring frequency of 50 Hz and the introduction of lime kiln gas. When the conductivity of the reaction slurry B is measured to be 2.1, the introduction of lime kiln gas is stopped to obtain a reaction slurry C, wherein the flow rate of the lime kiln gas is 0.4 m 3 / min, the volume fraction of carbon dioxide in the lime kiln gas is 36.7%;

[0052] Step 103. Secondary aging:

[0053] Adding ammonium bicarbonate to the reaction slurry C obtained in step 102, aging at 95° C. and stirring at 20 Hz for 48 hours to obtain a reaction slurry D, wherein the amount of ammonium bicarbonate added is 4% of the dry weight of calcium carbonate;

[0054] Step 104. Secondary crystal form control:

[0055] After the reaction slurry D obtained in step 103 is diluted to a concentration of 1.05 mol / L, 1.3% sorbitol on a dry basis of calcium carbonate is added at 42° C., and a reaction slurry E is obtained after a pre-reaction of 18 minutes. The reaction slurry E is transferred to a high shear carbonization kettle, and secondary carbonization is carried out under the condition that the conductivity is 2.1 and lime kiln gas is continuously introduced. When the pH value of the reaction slurry E is measured to be 7.0, the introduction of lime kiln gas is stopped to obtain a calcium carbonate slurry, wherein the reaction slurry E is divided into two parts, one of which is directly transferred to the carbonization kettle, and lime kiln gas is continuously introduced therein at a flow rate of 0.4 m 3 / min, the volume fraction of carbon dioxide in the lime kiln gas is 36.5%, and the other part is passed through the spiral nozzle at 0.8m 3 The output flow rate of / min is sprayed into the carbonization kettle;

[0056] Step 105. Homogenization and milling:

[0057] After adding a homogenizing dispersant to the calcium carbonate slurry prepared in step 104, stirring for 40 minutes at room temperature and a stirring frequency of 19 Hz, the mixture is transferred to a homogenizing tank for homogenization. The homogenized slurry is sequentially dehydrated, dried, crushed and classified to obtain pigment-grade large cubic ultrafine precipitated calcium carbonate, wherein the homogenizing dispersant is a mixture of a phosphate ester and a HOMOGENOLL-18 polycarboxylic acid surfactant in a mass ratio of 4:1, and the amount of the homogenizing dispersant added is 3.5% of the dry weight of the calcium carbonate.

[0058] Example 3

[0059] A method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate comprises the following steps:

[0060] Step 101. Primary aging:

[0061] Quicklime with a whiteness of 95 degrees and water are sequentially added into a reactor in a mass ratio of 1:7 to obtain reaction slurry A after digestion, and the reaction slurry A is filtered through a 200-mesh vibrating screen and transferred to a three-stage suspension separator for impurity removal, and after impurity removal, it is filtered through a 325-mesh vibrating screen to obtain high-whiteness calcium hydroxide refined slurry, and the high-whiteness calcium hydroxide refined slurry is aged;

[0062] Step 102. Primary crystal form control:

[0063] After the aged high-whiteness calcium hydroxide refined slurry in step 101 is diluted to a concentration of 1.2 mol / L, 1.5% xylitol by dry weight of calcium carbonate is added at 45° C., and a reaction slurry B is obtained after a pre-reaction for 21 minutes. The reaction slurry B is transferred to a high-shear carbonization kettle, and carbonized once under the condition of stirring frequency of 63 Hz and passing lime kiln gas. When the conductivity of the reaction slurry B is measured to be 2.1, the passing of lime kiln gas is stopped to obtain reaction slurry C, wherein the flow rate of lime kiln gas is 0.5 m 3 / min, the volume fraction of carbon dioxide in the lime kiln gas is 37.7%;

[0064] Step 103. Secondary aging:

[0065] Adding ammonium bicarbonate to the reaction slurry C obtained in step 102, aging at 96° C. and stirring at 25 Hz for 48 hours to obtain a reaction slurry D, wherein the amount of ammonium bicarbonate added is 5% of the dry weight of calcium carbonate;

[0066] Step 104. Secondary crystal form control:

[0067] After the reaction slurry D obtained in step 103 is diluted to a concentration of 1.2 mol / L, sorbitol in an amount of 1.3% by dry weight of calcium carbonate is added at 45° C., and a reaction slurry E is obtained after a pre-reaction for 22 minutes. The reaction slurry E is transferred to a high shear carbonization kettle, and secondary carbonization is performed under the condition that the conductivity is 2.3 and lime kiln gas is continuously introduced. When the pH value of the reaction slurry E is measured to be 7.0, the introduction of lime kiln gas is stopped to obtain a calcium carbonate slurry, wherein the reaction slurry E is divided into two parts, one of which is directly transferred to the carbonization kettle, and lime kiln gas is continuously introduced therein at a flow rate of 0.5 m 3 / min, the volume fraction of carbon dioxide in the lime kiln gas is 37.8%, and the other part is passed through the spiral nozzle at 0.8m 3 The output flow rate of / min is sprayed into the carbonization kettle;

[0068] Step 105. Homogenization and milling:

[0069] After adding a homogenizing dispersant to the calcium carbonate slurry prepared in step 104, stirring for 48 minutes at room temperature and a stirring frequency of 25 Hz, the mixture is transferred to a homogenizing tank for homogenization. The homogenized slurry is dehydrated, dried, crushed and classified in sequence to obtain pigment-grade large cubic ultrafine precipitated calcium carbonate, wherein the homogenizing dispersant is a mixture of a phosphate ester and a HOMOGENOLL-18 polycarboxylic acid surfactant in a mass ratio of 5:1, and the amount of the homogenizing dispersant added is 3.8% of the dry weight of the calcium carbonate.

[0070] Comparative Example 1

[0071] It is the common titanium dioxide (rutile type) on the market.

[0072] Comparative Example 2

[0073] It is common precipitated calcium carbonate on the market.

[0074] Comparative Example 3

[0075] It is nano calcium carbonate with a particle size range of 50-100nm that is common in the market.

[0076] Comparative Example 4

[0077] A mixture of the calcium carbonate crystals prepared in Example 3 and the titanium dioxide (rutile type) in Comparative Example 1 in a mass ratio of 1:1.

[0078] The pigment crystal samples mentioned in Examples 1-3 and Comparative Examples 1-4 were tested for whiteness and average particle size range, and the hiding power was tested as follows:

[0079] Step 201. Weigh 7 g of varnish (in a drinking cup), 3 g of varnish on a balance, and then add 2 g of the sample prepared in Example 1-3 and Comparative Example 1-4, and stir evenly with a glass rod for 5 minutes; prepare a standard sample in the same way;

[0080] Step 202. Use a glass rod to place the prepared paint paste on a white board of black and white cardboard, with the standard sample on the left and the sample on the right (the sample and the standard sample are basically parallel and there is a 3mm gap), and then use a wet film preparation device to scrape from the white board to the black board at 25μm;

[0081] Step 203. Place the cardboard horizontally in the room at room temperature for 1 day;

[0082] Step 204. First, measure the reflectivity of the coating on the white board, measure the four points of the top, bottom, left and right, and calculate the average value RW; then measure the coating on the blackboard, measure the four points of the top, bottom, left and right, and calculate the average value RB; the standard sample is also measured according to the above steps;

[0083] Step 205. Calculate the covering power: covering power index = RW / RB.

[0084] The test results are shown in Table 1 below:

[0085] Table 1 Test results of Examples 1-3 and Comparative Examples 1-4

[0086]

[0087] It can be seen from the test data in Table 1 above that the calcium carbonate crystals prepared in the present application can replace titanium dioxide by 50%. By adding different crystal control agents in the primary crystal control and secondary crystal control steps, during the primary crystal nucleus control process, the primary crystal control agent can be directionally adsorbed on the surface of calcium carbonate to induce the generation of cubic crystal nuclei. During the secondary crystal nucleus control process, the secondary crystal control agent undergoes a grafting reaction on the surface of the cubic crystal nucleus to further generate cubic calcium carbonate crystals with larger particle sizes, and the average particle size range of the calcium carbonate crystals is accurately controlled to 0.5-0.6 μm, thereby improving its hiding power and whiteness, and the whiteness can be greater than 98. It has the advantages of good dispersibility, concentrated particle size distribution, high whiteness, high strength, good rigidity, good toughness, simple and feasible process, low cost, and low price. It can partially replace titanium dioxide as a high-performance pigment, which is convenient for promotion and implementation.

[0088] The above are only embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing pigment-grade large cubic ultrafine precipitated calcium carbonate, characterized in that: The following steps are involved: Step 101. Primary aging: Quicklime with a whiteness of 93-95 degrees and water are sequentially put into a reactor in a mass ratio of 1:5-7 to obtain reaction slurry A after digestion, and the reaction slurry A is filtered through a 180-250 mesh vibrating screen and then transferred to a three-stage suspension separator for impurity removal. After the impurity removal is completed, it is filtered through a 280-350 mesh vibrating screen to obtain high-whiteness calcium hydroxide refined slurry, and the high-whiteness calcium hydroxide refined slurry is aged; Step 102. Primary crystal form control: After diluting the high-whiteness calcium hydroxide refined slurry after aging in step 101 to a concentration of 1.0-1.2 mol / L, a primary crystal form control agent is added at 40-45° C., and the primary crystal form control agent is xylitol. After pre-reaction for 10-25 minutes, a reaction slurry B is obtained. The reaction slurry B is transferred to a high shear carbonization kettle, and a primary carbonization is performed under the conditions of stirring frequency of 40-100 Hz and passing lime kiln gas. When the conductivity of the reaction slurry B is measured to be 1.5-2.5, the primary carbonization reaction is carried out to the end point, and the passing of lime kiln gas is stopped to obtain a reaction slurry C; Step 103. Secondary aging: Adding an aging dispersant to the reaction slurry C obtained in step 102, wherein the aging dispersant is ammonium bicarbonate, and the amount of the aging dispersant added is 3-5% of the dry weight of calcium carbonate, and aging for 36-72 hours at 90-100° C. and a stirring frequency of 15-30 Hz to obtain a reaction slurry D; Step 104. Secondary crystal form control: After diluting the reaction slurry D obtained in step 103 to a concentration of 1.0-1.2 mol / L, a secondary crystal form controller is added at 40-45° C., wherein the secondary crystal form controller is sorbitol, and a reaction slurry E is obtained after a pre-reaction of 10-25 min. The reaction slurry E is transferred to a high shear carbonization kettle, and secondary carbonization is performed under the condition that the conductivity is 1.5-2.5 and lime kiln gas is continuously introduced. During the secondary carbonization process, the pH value of the reaction slurry E is measured. When the pH value of the reaction slurry E is measured to be 6.5-7.0, the secondary carbonization reaction reaches the end point, and the introduction of lime kiln gas is stopped to obtain a calcium carbonate slurry; Step 105. Homogenization and milling: After adding a homogenizing dispersant to the calcium carbonate slurry prepared in step 104, stirring for 30-50 minutes at room temperature and a stirring frequency of 10-30 Hz, the slurry is transferred to a homogenizing tank for homogenization. The homogenized slurry is sequentially dehydrated, dried, crushed and classified to obtain pigment-grade large cubic ultrafine precipitated calcium carbonate with an average particle size range of 0.5-0.6 μm.

2. A method for preparing a pigment-grade large cubic ultrafine precipitated calcium carbonate according to claim 1, characterized in that: In step 102, the flow rate of lime kiln gas is 0.3-0.5m 3 / min, the volume fraction of carbon dioxide in the lime kiln gas is 35-38%.

3. A method for preparing a pigment-grade large cubic ultrafine precipitated calcium carbonate according to claim 1, characterized in that: In step 104, the reaction slurry E is divided into two parts, one of which is directly transferred to a high shear carbonization kettle, and lime kiln gas is continuously introduced thereinto. The lime kiln gas flow rate and the volume fraction of carbon dioxide in the lime kiln gas are the same as those in step 102, and the other part is sprayed into the high shear carbonization kettle through a spiral nozzle.

4. A method for preparing a pigment-grade large cubic ultrafine precipitated calcium carbonate according to claim 3, characterized in that: In step 104, the output flow rate of the spiral nozzle is 0.5-1m 3 / min.

5. The method for preparing a pigment-grade large cubic ultrafine precipitated calcium carbonate according to claim 1, characterized in that: In step 105, the homogenizing dispersant is a mixture of phosphate ester and HOMOGENOLL-18 polycarboxylic acid surfactant in a mass ratio of 3-5:1, and the amount of the homogenizing dispersant added is 3-4% of the dry weight of calcium carbonate.